2015
DOI: 10.1097/bot.0000000000000467
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Concepts for Fracture Fixation

Abstract: Application of the correct fixation construct is critical for fracture healing and long-term stability; however, it is a complex issue with numerous significant factors. This review describes a number of common fracture types, and evaluates their currently available fracture fixation constructs. In the setting of complex elbow instability, stable fixation or radial head replacement with an appropriately sized implant in conjunction with ligamentous repair is required to restore stability. For unstable sacral f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 77 publications
0
37
0
Order By: Relevance
“…LOCKED group results confirmed that a locking plate with a short-bridge span results in asymmetric interfragmentary motion that is deficient for callus formation. 3 , 13 , 16 , 26 Although one body weight loading may be excessive for early postoperative loading, it resulted only in 0.1-mm motion at the near cortex. This motion remained below the 0.2-mm motion threshold that has been established as the lower boundary for fracture motion required to promote callus formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LOCKED group results confirmed that a locking plate with a short-bridge span results in asymmetric interfragmentary motion that is deficient for callus formation. 3 , 13 , 16 , 26 Although one body weight loading may be excessive for early postoperative loading, it resulted only in 0.1-mm motion at the near cortex. This motion remained below the 0.2-mm motion threshold that has been established as the lower boundary for fracture motion required to promote callus formation.…”
Section: Discussionmentioning
confidence: 99%
“…ImageJ quantitative image analysis software developed by the National Institute of Health ( www.imagej.net ) was used to extract marker displacement and to calculate the average axial motion d A and shear motion d S between osteotomy surfaces in response to incremental load steps. Because plate bending induces different amounts of axial motion at the near cortex and far cortex, 26 axial motion d A was extracted individually for the near cortex (d A, NC ) from markers 1 and 3, and for the far cortex (d A, FC ) from markers 2 and 4, as depicted in Supplemental Digital Content 1 (see Figure , http://links.lww.com/BOT/A993 ). Construct stiffness S C was calculated by dividing the applied axial load by the axial motion d A at the midpoint between the near and far cortex, with d A = (d A, FC + d A, NC )/2.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous researches identified the advantage of this plating technique for distal distal-third tibia fractures; however, trials have observed the increased rate of prolonged healing for simple distal tibia fractures [5][6], thereby indicating the limitation of the locking plate for simple distal distal-third tibia fractures. A few studies revealed that locked plating constructs provided overly rigid fixation and inhibited micromotion at the fracture site, which may suppressed callus formation, resulting in delayed union, nonunion, and fixation failure [7][8][9][10]. Increasing the bridging span of the locking plate may be an effective method to decrease the stiffness and increase the interfragmentary micromotion [11].…”
mentioning
confidence: 99%
“…Unfortunately the biomechanics of fracture fixation can be complex, in part due to variations in bone quality, anatomy, and local loading conditions. Furthermore, a surgeon's toolkit includes multiple implants and fixation techniques, which must be narrowed to a single configuration for each case . Despite a general understanding that fracture geometry and fixation construct influence the biomechanics essential for proper and timely healing, fracture fixation construct selection remains a largely subjective topic among surgeons and is often linked to surgical training experience…”
mentioning
confidence: 99%
“…Furthermore, a surgeon's toolkit includes multiple implants and fixation techniques, which must be narrowed to a single configuration for each case. 3 Despite a general understanding that fracture geometry and fixation construct influence the biomechanics essential for proper and timely healing, fracture fixation construct selection remains a largely subjective topic among surgeons and is often linked to surgical training experience. 4 At present, most hip fractures are surgically stabilized using an intramedullary (IM) nail.…”
mentioning
confidence: 99%